Graphene-based materials for energy conversion - Sahoo, Nanda Gopal (2013)
With the depletion of conventional energy sources, the demand for renewable energy and energy-efficient devices continues to grow. As a novel 2D nanomaterial, graphene attracts considerable research interest due to its unique properties and is a promising material for applications in energy conversion and storage devices. Recently, the fabrication of fuel cells and solar cells using graphene for various functional parts has been studied extensively. This research news summarizes and compares the advancements that have been made and are in progress in the utilization of graphene-based materials for energy conversion.